2009
DOI: 10.1103/physreve.80.031708
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-crystal pumping in a cylindrical capillary with radial temperature gradient

Abstract: Dynamic field pumping principle has been developed utilizing the interactions of both the director and velocity fields and a temperature gradient inverted deltaT. The orientational dynamics in the hybrid-oriented liquid-crystal (HOLC) microvolume confined between two infinitely long coaxial cylinders under the influence of the radially directed inverted deltaT has been investigated. We have carried out a numerical study of a system of hydrodynamic equations including director reorientation, fluid flow, and tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…The objective of this section is to analyze the response of the nematic phase confined in the cylindrical micro cavity between two horizontal coaxial cylinders under the influence of the temperature gradient ∇T directed from the inner (outer) cooler (warmer) to outer (inner) warmer (cooler) cylinders [28]. Therefore, we are primarily interested here in describing how the temperature gradient across the microvolume cavity between two coaxial cylinders can produce the hydrodynamic flow v. It has been treated in the framework of the classical Ericksen-Leslie theory [16,17], supplemented by the thermomechanical correction of shear stress [7,15], and the entropy balance equation [18].…”
Section: Heat Driven Nematic Flow In Cylindrical Microfluidic Channelmentioning
confidence: 99%
“…The objective of this section is to analyze the response of the nematic phase confined in the cylindrical micro cavity between two horizontal coaxial cylinders under the influence of the temperature gradient ∇T directed from the inner (outer) cooler (warmer) to outer (inner) warmer (cooler) cylinders [28]. Therefore, we are primarily interested here in describing how the temperature gradient across the microvolume cavity between two coaxial cylinders can produce the hydrodynamic flow v. It has been treated in the framework of the classical Ericksen-Leslie theory [16,17], supplemented by the thermomechanical correction of shear stress [7,15], and the entropy balance equation [18].…”
Section: Heat Driven Nematic Flow In Cylindrical Microfluidic Channelmentioning
confidence: 99%
“…еще один параметр системы. В случае малых градиентов температуры ∇χ по сечению ЖК-полости безразмерное уравнение баланса энтропии может быть записано в виде [15]…”
Section: основные уравненияunclassified
“…In this case, the direction of hydrodynamic flow v is influenced by both the direction of heat flow and the character of the preferred anchoring of the average molecular direction n on the bounding surfaces. [6][7][8][9][10] On the other hand, in LC cells where director anchorings on the two bounding surfaces are the same, i.e., both strongly homeotropic or homogeneous, the LC microvolume remains quiescent under the influence of the temperature gradient. If homogeneously aligned LC ͑HALC͒ sample confined in a microvolume between two horizontal coaxial cylinders and subjected to both a temperature gradient ٌT, with the inner cylinder kept at a lower temperature than the outer one, and radially applied electric field E, then the microvolume HALC material settles down to a stationary flow regime in the horizontal direction.…”
Section: Introductionmentioning
confidence: 98%
“…[6][7][8][9][10][11] It has been shown that in the case of a hybrid-oriented LC cell, the magnitude of the hydrodynamic flow v excited by a temperature gradient ٌT is proportional to the tangential component of the thermomechanical stress tensor ͑ST͒ ij tm . In this case, the direction of hydrodynamic flow v is influenced by both the direction of heat flow and the character of the preferred anchoring of the average molecular direction n on the bounding surfaces.…”
Section: Introductionmentioning
confidence: 99%